A case of spontaneous gastric rupture in a 5 years girl (La Pediatria Medica e Chirurgica, 2014)
We describe a case of spontaneous gastric rupture in a child of 5 years old. The patient reached us in a serious condition; the anamnesis was negative for traumatic events or gastrointestinal disorders. An abdominal X-ray and CT scan revealed free air and fluid in the abdominal cavity, leading to the diagnosis of gastro-intestinal perforation. Submitted to urgent surgery, a rupture of the posterior wall of the stomach was found that was treated with gastrectomy â€œÃ  la demandeâ€. The surgery follow-up was regular. Morphological and immunohistochemical study showed some muscular abnormalities of the muscular gastric wall.
Keywords: Gastric rupture; gastrectomy; immunohistochemical study; muscular abnormalities